Paul Demont, La cité grecque archa ique et classique et l'idéal de tranquillité, Paris, Les Belles Lettres, 1990, 436 pp. ISBN 2-251-32633-2 (Minerva, 2019)
Review: Paul Demont, La cité grecque archa ique et classique et l'idéal de tranquillité, Paris, Les Belles Lettres, 1990, 436 pp. ISBN 2-251-32633-2